Kualitas Sumber Daya Manusia, Kejelasan Peran, dan Motivasi Kerja Terhadap Kinerja Pegawai Lembaga Pemasyarakatan Kelas IIB Bireuen - Panji Iskandar Panji Iskandar; Ibrahim Ibrahim; Hildani Hildani; Afriana Afriana (Aceh Cooperative Care, 2025)
The quality of human resources in government agencies is a necessity in carrying out the mandate of state servants to the community. This requires employees to work based on performance. It is also suspected that factors related to role clarity and work motivation impact performance. This study analyzed these factors using an associative method and a quantitative approach. The statistics used in the analysis were a multiple regression model. The study was conducted on employees at the Class IIB Bireuen Prison. The results showed: (1) there is a partial influence of human resource quality, role clarity, and work motivation on employee performance. (2) Simultaneously, human resource quality, role clarity, and work motivation contribute to an increase in employee performance of 75,9%.